Malayan chettiars and their activities, 1930-1940 - Tevi Nagalinggam, Kuna (Universiti Sains Malaysia, 1973)
It was even as early as at the time of the writing of Ptolemy'a geography at about A.D. 50 that there were instances of extensive expansion of Indian colonization and commerce, ranging from Burma "and Malaya to Indonesia and Indochina.